THE PROBLEM OF TEXT UNDERSTANDING AND PRODUCTION IN PERU - Ramos, Moises (2011)
This article seeks to explain the problem of literacy in Peru (1); it focuses on the lack of information regarding how children learn or acquire writing skills, which allows initial literacy. It proposes to universities and educational institutes to incorporate into their curricula a closest approach to child development, specifically the period of the first seven years, crucial in the reader and writer training. Also, it invokes to decline traditional practices, which determine the failure of active and reflective readers from initial education and explain in part why the university and Peruvian professionals read little or write short texts. Along this line, it outlines the difficulties of the student to use writing as a personal way of processing information and as a tool to interact with their environment. In the last section there is a list of the concepts and processes that should use an education that respect the evolutionary processes, affective and communicative ones, related to initial literacy. The psychogenesis of literacy it of great importance in order to understand the problem: this issue has political and economic implications, because if a child does not understand what he/she reads he/she will be limited in their employment opportunities; at the same time, a developing society with poor levels of reading comprehension, such as Peru, will have complications when inserting in a globalized economy.